Erythrodermic psoriasis successfully and rapidly treated with brodalumab: Report of two cases. Issue 6 (10th October 2020) - Megna, Matteo; Fabbrocini, Gabriella; Ferrillo, Maria; Cinelli, Eleonora
Abstract: Erythrodermic psoriasis (EP) is a rare form of the disease clinically characterized by a generalized erythema covering ≥90% of the body surface area (BSA). The management of EP is challenging: no standardized guidelines exist with literature suggesting cyclosporine or infliximab as first‐line therapy. However, a recent systematic review showed a positive response in EP patients treated with biologic agents. The most common biologic used for EP up until now has been ustekinumab, whereas infliximab might represent a first‐line option in case of complicated EP (acute, severe, or unstable). Up until now, no case of brodalumab (a monoclonal antibody blocking IL‐17 receptor) treatment for EP in real‐life has ever been described. Here, we report the first two cases of efficacy and safety of brodalumab in real‐life cases of EP.